#bodypositivity: A content analysis of body positive accounts on Instagram. (June 2019) - Cohen, Rachel; Irwin, Lauren; Newton-John, Toby; Slater, Amy
Highlights: Body positive Instagram posts depicted a broad range of body types and appearances. Two fifths of posts contained an appearance-focused theme. Majority of posts aligned with theoretical definitions of positive body image. Abstract: In the last decade, the body image literature has begun to extend beyond a primary focus on body image disturbances and examine the construct of positive body image. Similarly, "Body positivity" is a growing social media trend that seeks to challenge dominant societal appearance ideals and promote acceptance and appreciation of all bodies and appearances. The present study provides a content analysis of body positive posts on Instagram. A set of 640 Instagram posts sampled from popular body positive accounts were coded for physical appearance-related attributes and central themes featured. Results showed that body positive imagery typically depicted a broad range of body sizes and appearances. Additionally, while a proportion of posts were appearance-focused, the majority of posts conveyed messages aligned with theoretical definitions of positive body image. This study clarifies body positive content on Instagram, as well as highlights points of overlap and distinction from academic principles of positive body image and other appearance-focused social media content. Accordingly, the results offer theoretical and practical implications for future research and prevention efforts.